1999
DOI: 10.1038/sj.bjc.6990133
|View full text |Cite
|
Sign up to set email alerts
|

Induction of MDR1 gene expression by anthracycline analogues in a human drug resistant leukaemia cell line

Abstract: SummaryThe effects of 4-demethoxydaunorubicin (idarubicin, IDA) and MX2, a new morpholino-anthracycline, on up-regulation of the MDR1 gene in the low-level multidrug resistant (MDR) cell line CEM/A7R were compared at similar concentrations (IC 10 , IC 50 and IC 90 ) over a short time exposure (4 and 24 h). The chemosensitivity of each drug was determined by a 3-day cell growth inhibition assay. Compared with epirubicin (EPI), IDA and MX2 were 17-and eightfold more effective in the CEM/A7R line respectively. No… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 31 publications
2
16
0
Order By: Relevance
“…A MDR variant CEM/A7R cell line, developed by DOX selection of T-cell lymphoblastic leukaemia CCRF-CEM cell line (Zalcberg et al, 1994), has been successfully used as a model to study the molecular mechanisms underlying regulation of drug resistance. A rapid upregulation of MDR1 gene in CEM/A7R cell line was induced by anthracyclines and its analogues (Hu et al, 1995(Hu et al, , 1999b, and prevented by CyA and its analogue PSC 833 (Hu et al, 1996). These results represent the clinical development of Pgp-mediated drug resistance during chemotherapy (Hu et al, 1999a).…”
mentioning
confidence: 80%
“…A MDR variant CEM/A7R cell line, developed by DOX selection of T-cell lymphoblastic leukaemia CCRF-CEM cell line (Zalcberg et al, 1994), has been successfully used as a model to study the molecular mechanisms underlying regulation of drug resistance. A rapid upregulation of MDR1 gene in CEM/A7R cell line was induced by anthracyclines and its analogues (Hu et al, 1995(Hu et al, , 1999b, and prevented by CyA and its analogue PSC 833 (Hu et al, 1996). These results represent the clinical development of Pgp-mediated drug resistance during chemotherapy (Hu et al, 1999a).…”
mentioning
confidence: 80%
“…Evidence from cell lines and in vivo studies of patients undergoing chemotherapy demonstrate that MDR1 can be rapidly upregulated following exposure to chemotherapeutic drugs (Chaudhary and Roninson, 1993;Hu et al, 1995Hu et al, , 1999aAbolhoda et al, 1999), supporting the activation model. For example, ex vivo treatment of AML blasts isolated from newly diagnosed patients prior to induction chemotherapy resulted in the rapid upregulation of MDR1 expression, concomitant with increases in Pgp expression within 16 h of treatment, and in one AML patient increased Pgp expression in vivo was observed after only 4 h of chemotherapy (Hu et al, 1999a).…”
Section: Introductionmentioning
confidence: 86%
“…For example, ex vivo treatment of AML blasts isolated from newly diagnosed patients prior to induction chemotherapy resulted in the rapid upregulation of MDR1 expression, concomitant with increases in Pgp expression within 16 h of treatment, and in one AML patient increased Pgp expression in vivo was observed after only 4 h of chemotherapy (Hu et al, 1999a). Furthermore, cells isolated from five patients undergoing lung perfusion with doxorubicin were shown to increase in MDR1 expression within as little as 50 min after treatment commencement (Abolhoda et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our laboratory has shown that, in five of five patients with metastatic sarcoma, tumor MDR1 RNA levels increased up to 10-fold within 50 min of exposure to the DNA-damaging agent doxorubicin (5). In a separate study, an increase in Pgp expression was observed in a patient with acute myeloid leukemia after 4 and 12 h of administration of daunorubicin͞AraC (19). Thus, inducible expression of MDR1 by toxic agents such as chemotherapy and radiation may play a major role in the development of clinical drug resistance, and ET-743 is the first agent identified with the potential for blocking this activation.…”
Section: Discussionmentioning
confidence: 99%